Pelatihan Pembuatan Content Management System (CMS) Prestashop di SMK Ihyaul Ulum Gresik - Wahyu Andy Prastyabudi; Titus Kristanto; Mohammad Sholik (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
The development of the world of information technology (IT) in the industrial era 4.0, which is increasing, brings new opportunities for society, and there are no limits to creating new business opportunities through digital media. Special abilities and skills are needed to create a simple online store so that it becomes a positive point for someone starting a new business, especially for someone who doesn't have an offline store yet. The problem faced by the students of Ihyaul Ulum Gresik Vocational School is that they don't have a shop yet, but the students are willing and have a business spirit. Based on the problems faced by the students, the service team provided training for Ihyaul Ulum Gresik Vocational High School students in the form of creating an online store using the Prestashop Content Management System (CMS). The training material is in the form of an explanation of the stages in creating an online store with Prestashop and business strategies through digital media. The results of the community service activities are that students gain knowledge, experience, and skills in creating online stores with Prestashop and can implement marketing through online media.